(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The climatic problems of human development in modern conditions are analyzed in the article. It is proved that the warming of the climate is a major climatic threat to modern world civilization, therefore it is necessary to maintain its level within 1.5 degrees (according to the terms of the Paris Agreement), which can not be achieved yet. It has been discovered that the solution of this problem can not be in transfer of «dirty production» in the climatic plan from developed countries to less developed, since their emissions of greenhouse gases lead to global warming of the planet. It has been found that it is necessary to find new approaches to solving global climate change problems and to identify financial resources for this interstate, state, regional, local level, as well as at household level. One of the directions of international cooperation in combating climate change should be the restriction of the use of toxic (environmentally-harmful and workers) investments from the developed countries to less developed countries and negatively affect the ecology of these countries. It is substantiated that toxic investments represent such investments that cause significant damage to the environment, climate and workers’ health. According to different classification grounds, it is expedient to divide them into several groups and subgroups: 1) environmental and social plus combined (ecological and social); 2) foreign and domestic; 3) state and private; 4) antihuman (or immoral). It is proved that combating climate change requires the use of a comprehensive financial climate mechanism that should include a range of financial incentives and fines: international climate investments and innovations, carbon tax, carbon quotas, «green» tariffs, «warm» loans, «green» bonds, loans from «green» banks, etc. In Ukraine, it is expedient to attract free funds from households that are still outside banks and other financial institutions and to direct them to the development of local energy cooperatives (example of developed countries). It was revealed that an important direction in overcoming the shortcomings in the use of the green tariff in Ukraine could be the restriction of monopoly in the field of production and use of renewable energy sources and the transition to the auctioning of green energy. It is substantiated that the Ukrainian authorities need to develop a system of incentives to attract foreign and domestic climatic investments, primarily to the development of renewable energy sources. But an unstable political and economic situation in the country, a complicated legislative framework are not conducive to this.